Sinoatrial nodal disease presenting with tachy-bradycardia syndrome in a fetus of anti-SSA/SSB-positive mother - Balaganesh Karmegaraj (Wolters Kluwer Medknow Publications, 2022)
Tachy-bradycardia syndrome (TBS) has been reported rarely in the fetus. We present here an unusual dominant involvement of sinoatrial node in a fetus presenting with TBS of anti-Sjögren'syndrome-related antigen A (SS-A) and antigen B (SS-B) autoantibodies positive mother. Prenatal imaging findings, Doppler hemodynamics, and outcomes are described.